Plexiform fibrohistiocytic tumor: a clinicopathological and immunohistochemical study of 39 tumors, with evidence for a CSF1-producing “null cell” population - Thangaiah, Judith Jebastin; Dashti, Nooshin K.; Agaimy, Abbas; Fritchie, Karen; Folpe, Andrew L. (Virchows Archiv, 2022)
Plexiform fibrohistiocytic tumor (PFHT) is a mesenchymal tumor of intermediate malignancy, typically occurring in the superficial soft tissues of young patients and displaying a biphasic pattern, with nodules of histiocytoid cells surrounded by fascicles of myofibroblastic spindled cells. The pathogenesis of PHFT is unknown. We comprehensively studied 39 PFHT, occurring in 25 females (66%) and 13 males (34%), ranging from 2 to 55 years of age (median 21 years). The tumors most often occurred in the upper extremity (n = 16, 41%) and ranged from 0.4 to 6.1 cm in size (median 1.5 cm). One patient with known neurofibromatosis type 1 presented with metachronous tumors of the finger and back. Clinical follow-up (29 patients; range 5–168 months; median 60 months) showed 3 tumors to have recurred locally; none was metastasized. One patient died of an unrelated cause; all others were alive without disease at the time of last follow-up. Immunohistochemistry showed the histiocytoid nodules of all cases to contain CD163/CD11c-positive histiocytes and cells negative for both markers (“null cells”). CSF1 expression was present in “null cells” in 7/10 cases (RNAscope chromogenic in situ hybridization). The Ki-67 labeling index was very low (< 5%); Ki-67-positive cells within histiocytoid nodules appeared to represent “null cells.” All tested cases were negative for significant mutations or fusion events (TruSight Mutation Panel, TruSight Fusion Panel, Mayo Clinic Melanoma Targeted Gene Panel). We conclude that PHFT may be even more indolent than has been appreciated, although classification as an “intermediate” tumor is correct. We hypothesize that the CSF1-producing “null cells” of PHFT may represent the neoplastic element, with the bulk of the tumor masses comprising recruited and reactive cell populations.
CRIS-Team Scopus Importer:2022-09-16
Keywords: CD11c; CD163; Chromogenic in situ hybridization; CSF1; Immunohistochemistry; Molecular genetics; Plexiform fibrohistiocytic tumor